Remediación de suelos contaminados con plomo (11) por fitotecnologías correctivas - Medicago sativa L. (Alfalfa) (2014)
The concentration of lead varies and depends on the situation. Naturally the lead presents a concentration of 1 0-50mg/kg, but, activity human increases in 10 to 200 more; atmospheric lead approximates to 1 O~g/m3 of air; lead dissolved in water Bogotá river (Colombian) a concentration of 49,77 KgPb/ day. Is used as a plant species acumulation a Medicago Sativa L. The soils of the Agricultural Center Marengo the Universidad Nacional of Colombia; Bogota headquarters, were used for experimentation, taking into account that said inside Center circulates an irrigation canal which is fed with water from the middle of the Bogotá River basin. Collection of soils in situ, and his study was carried out in vitro in the Agustín Codazzi Geographical Institute.